Comparative Efficacy of Amprolium, Toltrazuril and Neem Leaf Powder against Caprine Coccidiosis - Awasthi, Shivam; Bagherwal, Rajendra K.; Mehta, Hemant K.; Jayraw, Anant K.; Singh, Rajveer (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Coccidiosis is commonly observed in kids shortly after weaning because of the stress due to sudden separation from their dam. The  objective of the study was to assess the comparative efficacy of amprolium, toltrazuril and neem leaf powder against caprine coccidiosis.  In the present study, based on oocyst per gram (OPG) values, it was found that toltrazuril is more efficacious than amprolium as reduction  in OPG was higher in toltrazuril treated kids (97.81%) when compared with amprolium treated kids (95.83%). The efficacy of neem leaf  powder was recorded as 57.62%. Significantly higher (p
Keywords: Body weight gain; Coccidiosis; Efficacy; Kids; oocyst per gram (OPG)